Теоретичні передумови оптимізації сукупних термореновацій при проведенні енергетичного аудиту будинку - Возняк, О.; Юркевич, Ю.; Желих, В. (Видавництво Національного університету «Львівська політехніка», 2003)
In this article scientifically proved results of civil buildings energetic audit carrying out method optimization are presented. Ways of thermorenewal process quantity needed for consideration reducing at energy audit carrying out are proposed. Quantity estimation of this reducing energy audit method is presented, taking into account modern economic calculating methods and modern economic efficiency estimation method. Quantity estimation of microclimate providing system save energy and efficiency of heat during heating season in comparison with a traditional heating regime is done.